2013
DOI: 10.1002/jwmg.497
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between grazing and waterfowl production in the Canadian prairies

Abstract: The survival of waterfowl nests is positively correlated with the amount of grassland on the landscape, and population growth rates of some waterfowl species (e.g., mallards [Anas platyrhynchos]) are sensitive to nest survival rates. Thus, the effect of actions that alter grassland vegetation physiognomy, such as grazing, on waterfowl production is of interest to waterfowl habitat managers. Additionally, grasslands contribute other ecological goods (e.g., forage for livestock and wildlife) and services (e.g., … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 30 publications
1
31
2
Order By: Relevance
“…Tierney et al (1998);Friberg et al (1998);Sievers et al (2017) Reforestation-it may be assumed that on balance the impacts of reforestation using native species should be positive for freshwater biodiversity in the . (2019);Bloom et al (2013);Abell et al (2019);Beltran et al (2011);Hein et al (2018) …”
mentioning
confidence: 99%
“…Tierney et al (1998);Friberg et al (1998);Sievers et al (2017) Reforestation-it may be assumed that on balance the impacts of reforestation using native species should be positive for freshwater biodiversity in the . (2019);Bloom et al (2013);Abell et al (2019);Beltran et al (2011);Hein et al (2018) …”
mentioning
confidence: 99%
“…The closely related blue-winged teal has similarly been shown to select nest sites in grassland rather than sites with other plant compositions (Klett et al 1988). The availability of grasslands is often associated with increased nest survival rates, but the direct effects of forbs at a nest site have not been frequently quantified for waterfowl (Stephens et al 2005, Thompson et al 2012, Bloom et al 2013. Studies examining the effects of forbs at nesting sites have indicated that the presence of forbs can result in higher probabilities of selection and nest survival of ground-nesting species (Arnold et al 2007, Arbeiter and Franke 2018, Sherfy et al 2018, Dixon et al 2019, Lautenbach et al 2019.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between animal grazing and freshwater ecosystems is complicated. Because grasslands can require natural disturbance or active management to prevent succession to forest, grazing at certain levels and times of the year may be an appropriate and necessary activity in some systems, and can contribute to maintaining native freshwater biodiversity (Bloom, Howerter, Emery, & Armstrong, 2013;Marty, 2015;Mester, Szalai, Mero, Puky, & Lengyel, 2015); however, overgrazing can have impacts on sediment and nutrient delivery, as well as on hydrology. Furthermore, livestock congregating in riparian zones and entering streams in order to cross or gain access to water can have direct impacts on stream banks and can introduce bacterial and nutrient contaminants into the water, as well as increase sediments (Fitch & Adams, 1998).…”
Section: Ranching Best Management Practicesmentioning
confidence: 99%